Three-dimensional simulation and inversion of borehole temperatures for reconstructing past climate in complex settings - Hopcroft,PO; Gallagher,K; Pain,CC; Fang,F (JOURNAL OF GEOPHYSICAL RESEARCH-EARTH SURFACE, 2009)
An understanding of the way that ground surface temperatures have changed with time contributes to our knowledge of past climate change. One approach that has been used to achieve this is to relate deviations in borehole temperature depth profiles to past ground surface temperatures. This paper describes a new computationally efficient reduced order approach that eliminates problems associated with very localised borehole terrain affects. This approach expands upon a world-leading expertise in reduced order modelling methods and facilitates the use of a much broader range of geothermal data to be used for palaeoclimate reconstruction purposes.